Pima Variety Test, Marana, 1995 - Thacker, G. (College of Agriculture, University of Arizona (Tucson, AZ), 1996)
Four Pima varieties were grown in a replicated trail on the Evco Farm in Marana. There were no significant differences in lint yield.